Prospects of Global Navigation Satellite System (GNSS) reflectometry for geodynamic studies - Shum, C. K.; Lee, Hyongki; Abusali, P. A. M.; Braun, Alexander; de Carufel, Guy; Fotopoulos, Georgia; Komjathy, Attila; Kuo, Chungyen (Advances in Space Research, 2011)
Innovative processing of satellite radar altimetry over solid Earth has been successfully applied for observing geodynamic process of glacial isostatic adjustment over the former Laurentide Ice Sheet in the present-day Hudson Bay land region. In this contribution, a simulation is conducted to study the prospects of the applications of space-/airborne and land-based Global Navigation Satellite System (GNSS) reflectometry to synoptically observe global-scale geodynamic processes with a vertical accuracy of similar to 2 mm/yr. (C) 2010 COSPAR. Published by Elsevier Ltd. All rights reserved.